Social and professional influences on antimicrobial prescribing for doctors-in-training: a realist review - Papoutsi, C; Mattick, K; Pearson, M; Brennan, N; Briscoe, S; Wong, G (Oxford University Press, 2017)
Background: Antimicrobial resistance has led to widespread implementation of interventions for appropriate prescribing. However, such interventions are often adopted without an adequate understanding of the challenges facing doctors-in-training as key prescribers. Methods: The review followed a realist, theory-driven approach to synthesizing qualitative, quantitative and mixed-methods literature. Consistent with realist review quality standards, articles retrieved from electronic databases were systematically screened and analysed to elicit explanations of antimicrobial prescribing behaviours. These explanations were consolidated into a programme theory drawing on social science and learning theory, and shaped though input from patients and practitioners. Results: By synthesizing data from 131 articles, the review highlights the complex social and professional dynamics underlying antimicrobial prescribing decisions of doctors-in-training. The analysis shows how doctors-in-training often operate within challenging contexts (hierarchical relationships, powerful prescribing norms, unclear roles and responsibilities, implicit expectations about knowledge levels, uncertainty about application of knowledge in practice) where they prioritize particular responses (fear of criticism and individual responsibility, managing one’s reputation and position in the team, appearing competent). These complex dynamics explain how and why doctors-in-training decide to: (i) follow senior clinicians’ prescribing habits; (ii) take (or not) into account prescribing aids, advice from other health professionals or patient expectations; and (iii) ask questions or challenge decisions. This increased understanding allows for targeted tailoring, design and implementation of antimicrobial prescribing interventions. Conclusions: This review contributes to a better understanding of how antimicrobial prescribing interventions for doctors-in-training can be embedded more successfully in the hierarchical and inter-professional dynamics of different healthcare settings.